The statistical average of optical properties for alumina particle cluster in aircraft plume. (April 2018) - Li, Jingying; Bai, Lu; Wu, Zhensen; Guo, Lixin
Highlights: Based on multi-sphere T matrix method, a method for finding the statistical average optical properties of alumina particle clusters in plume is proposed. The effect of different distributions and different detection wavelengths on the statistical average optical properties of alumina particle cluster is discussed. The statistical average optical properties under the alumina particle cluster model established in this study and those under three simplified alumina particle models are compared. The research results have a great effect on modeling IR and UV radiation properties of plume. Abstract: We establish a model for lognormal distribution of monomer radius and number of alumina particle clusters in plume. According to the Multi-Sphere T Matrix (MSTM) theory, we provide a method for finding the statistical average of optical properties for alumina particle clusters in plume, analyze the effect of different distributions and different detection wavelengths on the statistical average of optical properties for alumina particle cluster, and compare the statistical average optical properties under the alumina particle cluster model established in this study and those under three simplified alumina particle models. The calculation results show that the monomer number of alumina particle cluster and its size distribution have a considerable effect on its statistical average optical properties. The statistical average of optical properties for alumina particle cluster at common detection wavelengths exhibit obvious differences, whose differences have a great effect on modeling IR and UV radiation properties of plume. Compared with the three simplified models, the alumina particle cluster model herein features both higher extinction and scattering efficiencies. Therefore, we may find that an accurate description of the scattering properties of alumina particles in aircraft plume is of great significance in the study of plume radiation properties.